Individual dosimetry as an element of health prevention for employees exposed to ionizing radiation - Joanna Domienik-Andrzejewska; Marta Wiszniewska (Medycyna Pracy, 2023)
The paper presents the current radiation protection standards, in line with the recommendations of the International Commission on Radiological Protection (ICRP), and their evolution over the years based on new knowledge about the biological effects of ionizing radiation and the changing attitude of people to the accepted risk. The work takes into account in particular the role of the dose limit principle and individual dose measurements in activities aimed at health prevention of individual people occupationally exposed to ionizing radiation. Med Pr Work Health Saf. 2023;74(6):527–39.